Faktor-Faktor Yang Mempengaruhi Kepatuhan Wajib Pajak Kendaraan Bermotor di Kota Solok - Witra Maison; Rita Dwi Putri; Abdul Azis (Jurnal Ilmiah Raflesia Akuntansi, 2025)
The aim of this research is to determine the effect of administrative sanctions, tax socialization, and service quality on motor vehicle taxpayer compliance. This type of research is quantitative research to determine the influence of Tax Knowledge (X1), Taxpayer Awareness (X2), Service Quality (X3), and Tax Sanctions (X4) on Motor Vehicle Taxpayer Compliance (Y). The population in this study were taxpayers registered at the Solok City SAMSAT Office in 2020-2023 and the sample in this study used the Slovin formula, namely 100 motor vehicle taxpayers. The test results show that Tax Knowledge influences Motor Vehicle Taxpayer Compliance because it has a calculated t value of 2.126 > t table 1.985 with a significance of 0.036 < 0.05, Taxpayer Awareness influences Motor Vehicle Taxpayer Compliance because the calculated t value is 2.160 > t table 1.985 with a significance of 0.033 < 0.05, quality Tax Services have no effect on Motor Vehicle Taxpayer Compliance because the t value is 1.462 < t table 1.985 with a significance of 0.147 > 0.05, and Tax Sanctions have no effect on Motor Vehicle Taxpayer Compliance because the t value is 1.879 < t table 1.985 with a significance of 0.063 > 0.05.